Reforestation with Abies cephalonica Loudon: a five-year study of seedling survival. Issue 2 (14th March 2016) - Detsis, Vassilis; Efthimiou, Georgios; Theodoropoulou, Olga; Siorokou, Stavroula
Abstract : Purpose: – The purpose of this paper is to establish the effects on the survival of outplanted Abies cephalonica Loudon seedlings of seedling characteristics, site characteristics and management practices. Design/methodology/approach: – The study was carried out by repeatedly monitoring survival of seedlings during a five-year period as well as establishing statistical relationships with a set of variables belonging to the aforementioned categories. It took place in plots reforested after a wildfire in the Parnitha Mt. National Park, near Athens, Greece. Findings: – The odds of survival were found to be affected by bedrock type, dominant vegetation, initial seedling height and use of shading implements. Artificial shading was most important during the first year, site-related characteristics gained importance with increasing age and seedling height was of relatively constant importance. Shifts in temporal patterns of mortality and damage symptoms occurrence suggest that the mechanisms causing mortality changed with increasing age. Practical implications: – The use of large seedlings in reforestation projects involving A. cephalonica should be preferred. Shading improves survival but due to the high costs this technique could be reserved for unfavorable plots, e.g. on limestone. Planting A. cephalonica in marginal sites should be avoided. Originality/value: – The knowledge of the performance of A. cephalonica outplanted seedlings is very limited, while the need is increasing due to the spread of wildfires in this previously unaffected habitat.